Test accuracy of polymerase chain reaction methods against conventional diagnostic techniques for Cutaneous Leishmaniasis (CL) in patients with clinical or epidemiological suspicion of CL: Systematic review and meta-analysis. - Luz Estella Mesa; Rubén Manrique; Carlos Muskus; Sara M Robledo (Public Library of Science (PLoS), 2020)
BACKGROUND:Molecular diagnostic tests, notably polymerase chain reaction (PCR), are highly sensitive test for Leishmania detection, which is especially relevant in chronic cutaneous lesion with lower parasite load. An accurate diagnosis is essential because of the high toxicity of the medications for the disease. Nevertheless, diagnosis of cutaneous leishmaniasis (CL) is hampered by the absence of a reference standard. Assuming that the PCR-based molecular tools are the most accurate diagnostic method, the objective of this systematic review was to assess the diagnostic accuracy of PCR-based molecular tools in a meta-analysis of the published literature. METHODOLOGY/PRINCIPAL FINDINGS:A search of the published literature found 142 papers of which only 13 studies met the selection criteria, including conventional PCR, real-time PCR, Loop-mediated isothermal amplification (LAMP), recombinase polymerase amplification (RPA), polymorphism-specific PCR (PS-PCR). The sensitivities of the individual studies ranged from 61% to 100%, and specificities ranged from 11% to 100%. The pooled sensitivities of PCR in smears were 0.95 (95% CI, 0.90 to 0.98), and the specificity was 0.91(95% CI, 0.70 to 0.98). In general population, estimates were lower in aspirates, skin biopsies and swab samples with 0.90 (95% CI, 0.80 to 0.95) and 0.87 (95% CI, 0.76 to 0.94) for sensitivity and specificity, respectively. The specificity was lower in consecutive studies, at 0.88 (95% CI, 0.59 to 0.98) and its CI were wider. CONCLUSIONS/SIGNIFICANCE:No statistically significant differences between the accuracy in smears, aspirate, skin biopsies or swabs samples were observed. Therefore, a simple smear sample run by PCR, instead more invasive samples, may be enough to obtain a positive diagnosis of CL. The results for PCR in all samples type confirm previous reports that consider PCR as the most accurate method for the diagnosis of CL.